Evaluating test item quality: A comprehensive analysis of economics multiple-choice questions in Indonesian high schools (Case study at SMA Negeri 1 Gedangan) - Novan, Arsharil; Kamalia, Putri Ulfa (STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to evaluate the psychometric characteristics of multiple-choice question items in the daily assessment instrument of Economics subjects in phase F at SMA Negeri 1 Gedangan. The instrument was developed through the first three stages of a 4D model (Define, Design, Develop) and analyzed using the Classical Test Theory (CTT) approach. Content validity was tested using the Aiken's V index, while empirical validity, difficulty level, differentiation, trick effectiveness, and reliability were analyzed quantitatively. The validation results showed that nine out of ten questions had sufficient content validity (V ≥ 0.50), but one question was declared invalid and removed. Quantitative analysis showed that 90% of the questions were relatively easy (P > 0.80), 35% had good differentiation (D ≥ 0.40), and the reliability of the instrument was in the medium category (KR-20 = 0.692). Some tricksters do not function optimally, indicating the need for improvements in the design of the answer choice. These findings affirm the importance of question item analysis in improving the quality of economic learning evaluation, especially in supporting formative assessments in accordance with the principles of the Independent Curriculum.